TATA KELOLA KOLABORATIF DALAM PELAKSANAAN PELATIHAN DAN SERTIFIKASI MANAJEMEN APARATUR SIPIL NEGARA - Salbiah, Euis; Apriliani, Neng Virly; Nabilah, Siti; Seran, Gotfridus Goris; Pratidina, Ginung; Munjin, R. Akhmad; Sastrawan, Berry; Subagdja, Oetje (Universitas Djuanda, 2025)
Improving the quality of Human Resources for the State Civil Apparatus (ASN) is a fundamental step in enhancing the effectiveness of public service delivery amidst increasing demands for professionalism and adaptability. Collaborative governance is viewed as a strategic approach to address the complexity of implementing integrated and participatory training and certification programs for State Civil Apparatus (ASN). This study aims to analyze the implementation of collaborative governance in the management training and certification of ASN in 2024. A descriptive quantitative approach was employed, using purposive and total sampling techniques with 82 respondents comprising both participants and organizers. Data were collected through questionnaires and analyzed using the Weighted Mean Score (WMS) method. The results show that efforts to apply collaborative governance principles in ASN training have been initiated through inter-agency cooperation. However, the implementation has not fully reflected the theoretical framework, particularly Emerson et al. (2012), which emphasizes shared motivation, joint capacity for collective action, and mutual understanding of change. Furthermore, based on Kirkpatrick's training evaluation model, the impact of these efforts has not yet reached significant levels of behavioral change or measurable results. This indicates that the current application of collaborative governance remains partial and has yet to contribute optimally to the overall effectiveness of ASN training. The findings highlight a gap between theoretical concepts and field practices, providing a foundational basis for the development of a more applicable and impactful collaborative model for future ASN training initiatives.